Market Orientation, Digital Marketing, and Product Innovation Strengthen Competitive Advantage of Cake and Bakery SMEs - Agustina, Amanda Tri; Nuvriasari, Audita (Economic and Business Horizon, 2026)
The cake and bakery SME sector in Yogyakarta has experienced increasing competition due to shifting consumer preferences and the rapid adoption of digital platforms. In this context, understanding factors that enhance competitive advantage is crucial for business sustainability. This research seeks to analyze the impact of market orientation, digital marketing, and product innovation on the competitive advantage of cake and bakery small and medium-sized enterprises in the Special Region of Yogyakarta. A quantitative research approach was employed, involving 100 SME managers selected through purposive sampling. Primary data were collected using questionnaires distributed directly to respondents. Data analysis was conducted using multiple linear regression. The results indicate that market orientation, digital marketing, and product innovation each have a positive and significant impact on the competitive advantage of cake and bakery SMEs. These findings suggest that integrating market-oriented strategies, leveraging digital marketing, and continuously innovating products can strengthen SMEs’ competitiveness. The study provides practical recommendations for SME owners to enhance business performance and achieve sustainable competitive advantage in a dynamic market environment.